Impact of Temporal and Spatial Application Modeling on Event-Triggered Wireless Sensor Network Evaluation - Brisolara, Lisane; Ferreira, Paulo R.; Indrusiak, Leandro Soares (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2015)
This paper presents an approach for event-triggered wireless sensor networks (WSN) application modeling, aiming to evaluate the performance of WSN configurations with regards to metrics that are meaningful to specific application domains and respective end-users. It combines application, environment-generated workload and computing/communication infrastructure within a high-level modeling simulation framework, and includes modeling primitives to represent different kind of events based on different probabilities distributions. Such primitives help end-users to characterize their application workload and check the performance of specific WSN configurations when running realistic scenarios. Extensive experimental work shows that the proposed approach is effective in verifying whether a given WSN configuration can fulfill application non-functional requirements, as well as identifying the application behaviors that can lead a WSN to a break point after which it cannot further maintain application constraints.